Creative Conceptions of “Electronic Business: Sales and Financial Tools” for Economic Development - Simanauskas, Leonas (Ekonomika, 2007)
Traditional businesses all over the world have experienced very severe competition in terms of electronic commerce, or virtual retailing and financial service. mobile information and communication technology. etc. This has been compounded by rapid change within the telecommunication. IT and content sectors and throughout the relevant policy environment. The term “Electronic business” has been chosen by the author as the mo,t applicable generic term to define the growing salience of information with commercial activity.the purpose of L. Sodžiutė and V. Sūdžius monograph “Electronic business: Sales and Financial tools” is to describe what “Electronic business” is: how it is being conducted and managed; and its major opportunities, limitations, issues and risks.The economic issues are associated with electronic commerce and financial tools. such as its advantages and disadvantages, types of payment’ and information transfer security, the roles of organization and security facilities, to perform an analysis, to identify a forward level of electronic business and summarize the results of the analysis, and make suggestions for electronic commerce development facilities.The objective of taking this perspective is to give a business-focused understanding of the main issues involved in the development of electronic business, with the aim of introducing interested business people (both students and professionals) to the commercial and strategic impact of the information economy, especially in terms of comprehending how enterprises need to adjust if they are to sustain their competitive position.
Keywords: -